1990
DOI: 10.1007/bf00193016
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of kaempferol 3-O-glucoside into the cell walls of Norway spruce needles

Abstract: (14)C-Labelled CO2 fed to young Norway spruce (Picea abies [L.] Karst.) twigs was rapidly incorporated into kaempferol 3-O-glucoside (astragalin) of the needles. The patterns of the time course of total (per needle weight) and specific radioactivity (per amount of compound) of soluble and insoluble (cell wall-bound) astragalin indicate its transport from a soluble pool within the protoplast to an extraprotoplastic cell wall-bound pool within the needle. This conclusion is supported by measurements of the distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Continuous increase of cell wall-bound metabolite levels throughout the 2 years of needle development studied concomitant with the early transient maximum of the soluble, diacylated F3Gs (Figs 1 & 2) suggests that soluble metabolites are translocated and covalently bound to the cell wall. Similar observations exist for Norway spruce and other Pinaceae species (Strack et al 1989;Heilemann & Strack 1990;Schnitzler et al 1996;Fischbach et al 1999) as well as some Mediterranean evergreen broad-leaved trees (Liakoura, Manetas & Karabourniotis 2001). Based on fluorescence microscopic studies with trichomes of Quercus ilex and Olea europaea, it had been suggested that polyphenols are translocated from the perinuclear and cytoplasmatic space to cell walls during leaf ageing (Karabourniotis et al 1998).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…Continuous increase of cell wall-bound metabolite levels throughout the 2 years of needle development studied concomitant with the early transient maximum of the soluble, diacylated F3Gs (Figs 1 & 2) suggests that soluble metabolites are translocated and covalently bound to the cell wall. Similar observations exist for Norway spruce and other Pinaceae species (Strack et al 1989;Heilemann & Strack 1990;Schnitzler et al 1996;Fischbach et al 1999) as well as some Mediterranean evergreen broad-leaved trees (Liakoura, Manetas & Karabourniotis 2001). Based on fluorescence microscopic studies with trichomes of Quercus ilex and Olea europaea, it had been suggested that polyphenols are translocated from the perinuclear and cytoplasmatic space to cell walls during leaf ageing (Karabourniotis et al 1998).…”
Section: Discussionsupporting
confidence: 56%
“…The possible involvement of diacylated F3Gs in the process of cell‐wall deposition has been earlier indicated but was not further analysed (Strack et al . 1989; Heilemann & Strack 1990; Schnitzler et al . 1996; Fischbach et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The disappearance of these caffeic acid esters is due to either degradation, transport to an insoluble caffeic acid ester pool (cell wall? ; see Lam et al, 1992), as shown for a flavonol glucoside in Norway spruce needles (Heilemann and Strack, 1990), or translocation into another organ. In rhizomes a11 esters were detected in concentrations ranging from 0.1 to 0.8% of the dry weight over the entire growing season and winter (not documented).…”
Section: Substrate Specificitiesmentioning
confidence: 87%
“…Cell-wall-associated¯avonol glycosides have been detected in the needles of conifers (Strack et al 1989). In pulse-chase experiments 14 C-labeled CO 2 was incorporated into soluble kaempferol 3-O-glucoside which was detected 3 weeks later in an insoluble extracellular fraction (Heilmann and Strack, 1990). In other tracer studies using suspension-cultured plant cells,¯avonols with free 3-and 4¢-hydroxyl groups were degraded under speci®c conditions to 2,3-dihydroxy¯avones Muhle et al 1976) which could be further decomposed to form benzoic acid derivatives (HoÈ sel et al 1975;Miller and Schreier 1985).…”
Section: Introductionmentioning
confidence: 97%